Impacts of dietary arginine supplementation on performance, nutrient digestion and expression of proteins related to milk fatty acid and casein synthesis in early lactating dairy cows - Jing Zhang; Jiaojiao Lang; Lijun Bu; Yapeng Liu; Wenjie Huo; Caixia Pei; Qiang Liu (Animal Nutrition)
Arginine (Arg) can potentially increase milk yields in early lactating dairy cows by stimulating the development of mammary gland and the biosynthesis of milk proteins and fatty acids (FA); however, the underlying mechanism is still unclear. The hypothesis that rumen-protected Arg addition would increase milk, milk fat, and milk protein yields was tested, aiming to dlucidate the possible mechanism. Forty-eight multiparous Chinese Holstein dairy cows (milk yield 34.9 ± 1.27 kg/d, body weight 658 ± 12.7 kg, and days in lactation [DIL] 16.4 ± 2.56) were selected on the principle of proximity and blocked by DIL and milk yield, and divided into one of four groups in a randomized block design: control (without RPArg), low RPArg (LRPArg; 20 g/d Arg), medium RPArg (MRPArg; 40 g/d Arg), and high RPArg (HRPArg; 60 g/d Arg), 4 replicates per group and 3 cows per replicate and the experiment duration was 95 days, including a 10-d covariate period, a 15-d adaptation period, and a 70-d sampling period. The production of actual milk, energy-corrected milk, fat-corrected milk, milk fat, and milk protein linearly increased (P < 0.05) with RPArg provision. The yields of de novo FA and mixed FA in the milk linearly increased (P < 0.01), but that of preformed FA linearly decreased (P = 0.007). Supplementation with RPArg linearly increased the daily production of Arg, Asp, Cys, Glu, His, Met, Phe, Ser, Thr, and Trp (P < 0.05). With RPArg provision, serum contents of glucose, albumin, total protein, and nitric oxide linearly increased (P < 0.05); the levels of estradiol, prolactin, and insulin-like growth factor 1 quadratically increased (P < 0.01); and that of blood urea nitrogen quadratically decreased (P = 0.023). Furthermore, supplementation with 40 g/d Arg from RPArg promoted the expression of proteins implicated in mammary gland proliferation, FA synthesis, and milk protein synthesis. Thus, RPArg addition enhanced milk production, FA synthesis, and milk protein synthesis by promoting the expression of proteins involved in mammary gland development, FA synthesis, and milk protein synthesis.